Persepsi Mahasiswa Terhadap Pemilihan Capres dan Cawapres Pasca Pemilu 2024 di Universitas PGRI Jombang - Muslimin; Ananda Kholisotul Qolbiah; Najmuddin Maya'ba (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
Students, as part of a critical and educated group of young voters, often have political views that can influence election results. active participation of students in elections can improve the quality of democracy and strengthen the legitimacy of elected governments. The purpose of this research is To describe the perceptions of students as election committees towards the election of presidential and vice presidential candidates for the 2024 elections at PGRI University Jombang. The research method used in this research is descriptive qualitative. Data collection techniques using interviews and documentation. The data analysis technique in this study is the data reduction stage, data presentation and conclusions. The results of this study are (Students are vulnerable to the influence of information circulating and the influence of money politics